Measuring of Subjective and Objective Aesthetics in Planning and Urban Design - Al-Salam, Nadia A.; Al-Jaberi, Ahmed A.; Al-Khafaji, Ahmed S. (Civil Engineering Journal, 2021)
The article includes the concept of aesthetics through what has been dealt with in the literature by philosophers and researchers who have addressed this concept in an attempt to derive indicators of aesthetics. The article adopted a descriptive and analytical methodology by reviewing recent literature on the concept of aesthetics and its relation to urban planning and design issues. Many subjective and objective aesthetics indicators have been identified, some of which are classified under real aesthetics, and some under fake aesthetics. The indicators were applied to the Kufa Mosque complex and Sahla Mosque complex as a comparative case study. It was found that the indicators of real aesthetics have a higher weight in determining the final aesthetic judgment on the complex form versus the fake indicators, which in turn reinforced the weighting of the subjective aspect over the objective. This was consistent with the answer to the question directed to the sample about which complexes are more aesthetic. The answer was that the Kufa Mosque complex is most aesthetically. This was proven by the questions directed in the questionnaire, which outweighed the real aesthetic indicators for the Kufa Mosque complex. As for the results of analyzing the indicators of fake aesthetic were equal, as each complex achieved higher values in three indicators.Â Doi: 10.28991/cej-2021-03091743 Full Text: PDF